Self-perceived general health and its impact on oral health in the U.S. adult population: NHANES 2015–2018 - Fahad AlAli; Abdulrahman Al-Safi; Al-Jawharah Al-Ajmi; Fatemah Alshammari; Sarah Saqer; Woroud Al-Sulimmani; Ahmed Balkhoyor; Hend Alqaderi; Hend Alqaderi; Hesham Alhazmi (Frontiers in Oral Health)
IntroductionOral health is crucial to overall well-being and is often described as a “window to general health” due to the strong bidirectional relationship between the two. This paper aims to assess the relationship between self-perceived general health and oral health among U.S. adults.MethodsThis study analyzed data from the 2015–2018 NHANES, comprising 11,566 U.S. adults. Statistical analyses included weighted percentages, chi-square tests, and logistic regression to evaluate the relationships between self-perceived general health status and oral health predictors.ResultsEach unit increase in DMFT (decayed, missing due to caries, and filled teeth) resulted in a 2% increase in the odds of reporting fair to poor health compared with excellent to good health (p < 0.01). Additionally, for each additional decayed permanent tooth and each missing tooth, the odds of reporting fair to poor health compared with excellent to good health increased by approximately 38% (p = 0.004) and 43% (p = 0.010), respectively.ConclusionThis study suggests that higher DMFT scores, untreated dental decay, and missing teeth are associated with poorer self-perceived general health among U.S. adults. We recommend incorporating oral health assessments into general health check-ups, raising public awareness about their connection, and improving collaboration between medical and dental professionals to enhance patient care and preventive measures.